Animacy, anaphora and language change in Swedish - Skrzypek, Dominika (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper considers the role of animacy in the overt marking of indirect anaphors, i.e., noun phrases (NP), which introduce new discourse referents, that are grounded in the preceding discourse by means of a grounding element, an anchor. The indirect anaphors are considered in a diachronic perspective with reference to the emergent definite article and the variation between the article and other marking elements, in particular possessive pronouns. The study is based on an annotated corpus of Swedish prosaic texts from 1200–1550, which is a period of time when the definite article undergoes the process of grammaticalization in this language. The material was sorted according to the different combinations of the animacy of the anchor and the anaphor. The indirect anaphors which are anchored by means of expressions referring to animate entities show more variation of expression than those expressions referring to inanimate entities at the onset of definite article grammaticalization, but as the grammaticalization progresses, all indirect anaphors are by default expressed by the definite article. This is connected with the ongoing grammaticalization of the definite article and its extended use in new contexts.